Prognostic and predictive value of IDO expression in metastatic melanoma treated with Ipilimumab - Dagmar von Bubnoff; Christina Schmitt; Simone M. Goldinger; Dirk Schadendorf; Katharina C. Kähler; Christian Hafner; Nora Kramer; Waltraud Fröhlich; Reinhard Dummer; Carola Berking; Stefan Schliep; Michael C. Kirchberger; et al. (PLoS ONE, 2025)
Background The tumor microenvironment is crucial for prognosis and response to immunotherapy in several tumor entities. Methods In a multicenter retrospective study, a total of 86 tumor samples from patients with metastatic melanoma were evaluated for baseline expression of indoleamine 2,3-dioxygenase (IDO) and programmed death ligand 1 (PD-L1). Expression patterns of IDO and PD-L1 on tumor cells and antigen-presenting cells (APCs) as determined by immunohistochemical (IHC) staining of paraffin-embedded tissue sections were correlated with response to ipilimumab and overall survival (OS). Statistical analysis was performed using the Spearman correlation, the Mann-Whitney test and Kaplan-Meier estimator. Results IDO expression in tumor cells or APCs was not predictive for treatment response. The median OS was 26 months in IDO-positive and IDO-negative patients, regardless of IDO expression in tumor cells or APCs. A correlation of IHC expression scores of IDO and PD-L1 could not be documented. Conclusion The exact role of IDO in creating an immunosuppressive tumor environment and its reversal needs to be further elucidated.